(untitled) (Journal of Environmental Science and Natural Resources, 2015)
In recent years Bangladesh has experienced numerous winter events during the winter. In January 2010, northern and southwest parts of the country experienced a rapid fall in temperature with cold winds and dense fog. In January 2011 the Meteorological Department recorded the temperature as 2 to 5 degrees Celsius lower than the normal average temperature (about 10°C) during that time of the previous yearsresulting significant rise in respiratory illnesses, and in some cases deaths. Some prior arrangement should be made and preparatory measures should be taken by the respective departments, agencies to protect the affected people.Monitoring and prediction prior to the events is thus necessary. Satellite data are very useful for monitoring and analytical study of such natural events and their directional movement. SPARRSO monitors the formation, duration and movement of cold wave as one of its regular activities relating to disaster management, based on data received at its own ground station. In this paper,monitoring of winter events and their analytical study using satellite data will be discussed briefly. J. Environ. Sci. & Natural Resources, 8(1): 165-167 2015